Optimization of Diagnostics and Prevention of Dental Diseases in Industrial Workers - Masharipova N. A.; Xabibova N. N. (Researchparks Publishing, 2021)
Relevance. There is a high prevalence and intensity, first of all, of caries and periodontal diseases in trained workers of industrial enterprises, as well as a great need among them for dental treatment and prosthetics [Kabirova M.F., Usmanova I.N., 2009; Leonova L.E., Kamenskikh M.V., 2011; Leskov A.S., 2012; Saradzhev, V.V., 2005; Khavkina E.Yu., Olesov E.E., Maksyukov S.Yu., Makeev A.A., Rogatnev V.P., Magamedkhanov Yu.M., Kuznetsov A.V., Kolyabina Yu.V., 2011]. At the same time, most workers with long experience have general somatic diseases, low motivation to preserve dental health and adequate oral hygiene remains [Dubinina L.M., 2008; Kolyabina Yu.V., 2010; Kononenko V.I., Bronstein D.A., Olesov E.E., Khlutkov E.S., Yarilkina S.P., Kishko E.V., Zharov A.V., Rudakov V.A., 2012; Olesova V.N., Sorokoumov G.L., Balkarov A.O., Zakariev Z.Z., Pavlova N.A., Musheev I.U., 2007]. Large industrial enterprises have departmental medical services, including dental, and sanatorium facilities for the medical rehabilitation of their employees. The interaction of dentists at the workplace and in the sanatorium needs to be analyzed in modern conditions.